PRELIMINARY RESULTS OF COMPARATIVE PHARMACOECONOMIC PROSPECTIVE STUDY OF DIFFERENT THERAPIES OF ARTERIAL HYPERTENSION - E. I. Tarlovskaya; N. S. Maksimchuk; S. V. Malchikova; M. V. Avksentieva (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To carry out a comparative pharmacoeconomic analysis of two different types of antihypertensive therapy in patients with arterial hypertension (HT). Material and methods. 38 patients with essential HT (aged 18 to 70 years, 11 males and 27 females) associated with metabolic syndrome, and having a history of previous ineffective antihypertensive therapy were included into the study. The patients were randomized into 2 groups. Patients of V/A group received a fixed combination of valsartan and amlodipine (Exforge, Novartis) in dose of 5/160 and 10/160 mg depending on blood pressure (BP) level. Patients of L/A group received losartan (Lorista, KRKA) in dose of 100 mg and amlodipine (Tenox, KRKA) in dose of 5 and 10 mg. Treatment duration was 24 weeks. If target level of BP was not achieved during 12 weeks, indapamide retard was added to the therapies (Ravel SR, KRKA). Dinamics of BP and left ventricular mass index (LVMI) were considered. Cost-effectiveness method of analysis was used. Results. In V/A group 75% of patients achieved target BP levels for 24 weeks, while in L/A group — 33.3% of patients, and 16.7% of patients more after indapamide addition. L/A therapy cost was lower in comparison with this of V/A therapy: 57864.24 vs 156671.0 rubles per 24 weeks, respectively. Calculation shows that additional cost of 669.23 rubles during 24 weeks is needed to achieve BP target level in every next patient when V/A therapy is used instead of L/A therapy. LVMI reduction by 1% took 1015.13 rubles cost in V/A group and almost 6 times more in L/A group. Conclusion. Pharmacoeconomic analysis revealed that generic combination of L/A is the most cost-effective for BP reduction. Very low cost is required to achieve additional effect with original fixed V/A combination. V/A combination is the most economical for the left ventricular hypertrophy reduction. Thus, V/A combination is rational for use in HT patients with severe target-organs damage.